Enhancing interoceptive awareness in community-dwelling older adults: effects of a psychomotor intervention mediated by creative dance - Hugo Rosado; Hugo Rosado; Patrícia Motta; Ana Cruz-Ferreira; Ana Cruz-Ferreira; Catarina Pereira; Catarina Pereira (Frontiers in Psychology)
ObjectiveThis study aimed to investigate the effects of a psychomotor intervention mediated by creative dance on interoceptive awareness in community-dwelling older adults.MethodsThis 12-week non-randomized clinical trial involved 34 participants (74.6 ± 6.6 years), divided into two groups. The experimental group (EG) engaged in a psychomotor intervention (3×/week; 60 min/session), while the control group (CG) continued their usual daily activities. Interoceptive awareness was assessed using the Multidimensional Assessment of Interoceptive Awareness at baseline and post-intervention.ResultsWithin-group comparison showed significant improvements in the EG for the scales of Noticing, Not-Worrying, Attention Regulation, Emotional Awareness, Self-Regulation, and Trusting, (p < 0.05). Post-intervention comparison between groups revealed significant differences in all aforementioned scales (p < 0.05), except for Not-Worrying. Overall, the CG maintained or decreased their results. The improvements observed in the EG were clinically relevant, with effect sizes ranging from medium to large.ConclusionOur study results highlight the potential of a psychomotor intervention mediated by creative dance for enhancing interoceptive awareness in community-dwelling older adults, contributing to better emotional regulation and overall well-being. This effective intervention can be a valuable strategy for promoting healthy aging.